A potência das imagens em uma miscelânea amazônica: sociabilidade e estilo de vida nos Pássaros Juninos de Belém-Pará - SILVA, Eliane Suelen Oliveira da (Universidade Federal do Pará, 2011)
The Pássaros Juninos (Birds of june) or Bird melodrama-fantasy represent a type of musical theatre that is typical of Pará. They have elements of various theatre genres and regional manifesta¬tions as reference points, and bring to the surface sources from the African, Caucasian and indigenous cultures, which since the onset of colonisation in the region have miscigenated, resulting in what we now understand as being “Amazon culture”. This pa¬per intends to discuss the mestizo character that has engendered the circumstances of the appearance of the Pássaros Juninos, and, consequently, explain that such a manifestation evokes distinct images that converge in constructing fantastic Amazon narratives expressed in the form of sociabilities that are unique to the Pará context.